2018
DOI: 10.5539/elt.v11n6p1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Extensive Reading on English Vocabulary Learning: A Meta-analysis

Abstract: Extensive reading has been continuously studied as a promising instructional method for improving students’ language proficiency, including reading proficiency, vocabulary acquisition, and grammar awareness. The present study is a meta–analysis, which synthesized the data of 21 empirical studies (N = 1268). It was designed to explore whether extensive reading instruction was effective in improving students’ vocabulary acquisition, and if so, how the effectiveness varied in terms of the instruction length and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 30 publications
6
45
0
1
Order By: Relevance
“…Moreover, particularly interesting to the purposes of this study, literature shows that reading enhances vocabulary and spelling skills (Lee, Krashen, & Tse, 1997;Cho, Park, & Krashen, 2008). Similarly, Liu and Zhang (2018) analyzed the effectiveness of extensive reading on vocabulary learning in EFL environments, Results proved the significantly positive effect that extensive reading can have on English vocabulary learning. Hu and Nation (2000) also affirm that when the learner controls the reading skills, reading becomes a mean of vocabulary growth.…”
Section: The Effectiveness Of Reading For Vocabulary Learningmentioning
confidence: 94%
See 3 more Smart Citations
“…Moreover, particularly interesting to the purposes of this study, literature shows that reading enhances vocabulary and spelling skills (Lee, Krashen, & Tse, 1997;Cho, Park, & Krashen, 2008). Similarly, Liu and Zhang (2018) analyzed the effectiveness of extensive reading on vocabulary learning in EFL environments, Results proved the significantly positive effect that extensive reading can have on English vocabulary learning. Hu and Nation (2000) also affirm that when the learner controls the reading skills, reading becomes a mean of vocabulary growth.…”
Section: The Effectiveness Of Reading For Vocabulary Learningmentioning
confidence: 94%
“…Hence, graded readers are major means of learning from input, since they contain controlled vocabulary according to student's' English proficiency levels; that is why Liu and Zhang (2018) suggested that teachers should adopt graded readers as extensive reading books. Research has also shown that those students with access to books interest to them tend to read more and better (Krashen, 2004;McQuillan, 1998).…”
Section: Graded Readersmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from empirical research in English as a foreign or second language (EFL/ESL) contexts have consistently demonstrated that ER has positive effects on students’ reading speed and fluency (Huffman, 2014; Masrai & Milton, 2018; Nutalak, 2019; Suk, 2017), reading comprehension (Al Zeidi & Al Quraini, 2019; Al‐Homoud & Schmitt, 2009; Suk, 2017), reading motivation and attitude (Jang, Kang, & Kim, 2015; Karlin & Romanko, 2010; Suk, 2018), vocabulary acquisition (Al‐Homoud & Schmitt, 2009; Alsaif & Masrai, 2019; Chang & Hu, 2018; Liu & Zhang, 2018; Masrai & Milton, 2018; Suk, 2017), and critical thinking (Eftekhary & Kalayeh, 2014; Husna, 2019). Table 1 highlights some recent research on ER and its major findings.…”
Section: Introductionmentioning
confidence: 99%